Differential requirement for the N-terminal catalytic domain of the DNA polymerase ? p255 subunit in the mitotic cell cycle and the endocycle. - Suyari, O.; Kawai, M.; Ida, H.; Yoshida, H.; Sakaguchi, K.; Yamaguchi, M. (Gene, 2012)
In Drosophila, the 255kDa catalytic subunit (dpol?p255) and the 58kDa subunit of DNA polymerase ? (dpol?p58) have been identified. The N-terminus of dpol?p255 carries well-conserved six DNA polymerase subdomains and five 3'?5' exonuclease motifs as observed with Pol? in other species. We here examined roles of dpol?p255 during Drosophila development using transgenic fly lines expressing double stranded RNA (dsRNA). Expression of dpol?p255 dsRNA in eye discs induced a small eye phenotype and inhibited DNA synthesis, indicating a role in the G1-S transition and/or S-phase progression of the mitotic cycle. Similarly, expression of dpol?p255 dsRNA in the salivary glands resulted in small size and endoreplication defects, demonstrating a critical role in endocycle progression. In the eye disc, defects induced by knockdown of dpol?p255 were rescued by overexpression of the C-terminal region of dpol?p255, indicating that the function of this non-catalytic domain is conserved between yeast and Drosophila. However, this was not the case for the salivary gland, suggesting that the catalytic N-terminal region is crucial for endoreplication and its defect cannot be complemented by other DNA polymerases. In addition, several genetic interactants with dpol?p255 including genes related to DNA replication such as RFC, DNA primase, DNA pol?, Mcm10 and Psf2 and chromatin remodeling such as Iswi were also identified.